ChemInform Abstract: Valorization of Glycerol 1, 2‐Carbonate as a Precursor for the Development of New Synthons in Organic Chemistry. Issue 1 (3rd January 2013) - Bensemhoun, Julia; Condon, Sylvie
Abstract Activated glycerol carbonate derivatives (halogen or pseudohalide derivatives) such as (I) and (IV) are prepared and subjected to reactions with olefins (II).